Stability and uniform ultimate boundedness of solutions of a third-order differential equation (2010)
This paper is concerned with uniform ultimate boundedness of solutions of a third-order nonlinear differential equation (1.1). Sufficient conditions under which all solutions x(t), its first and second derivatives tend to zero as t —∞, when p(t,x,x',x") = 0, are presented.